Prediction for key damaged parts in steel bridge decks based on the stress influence area. (August 2020) - Yao, Yue; Ji, Bohai; Ye, Zhi; Fu, Zhongqiu; Zhu, Qi
Abstract: Preventive maintenance is one of the important development directions in maintenance engineering of steel bridge. To improve the pertinence of fatigue detection and preventive maintenance of steel bridge decks, a prediction method for key damaged parts was established. The process of method establishment and verification were described detailly, including a real bridge test, finite element analysis and theoretical calculation. During the process, the scopes of the stress influence areas and the stress characteristics of the vulnerable details on steel bridge deck were obtained. Through the application in practical engineering, the feasibility and validity of the method were well verified.